Fiscal Decentralization and Green Development Efficiency: Evidence From the New Capital “Nusantara” Buffer Zone - Fajri, Moh Najikhul; Pratama, Backtiar Putra; Kharisudin, Achmad (Bestuurskunde: Journal of Governmental Studies, 2023)
This paper aims to analyze the effect of fiscal decentralization on green development efficiency. This paper uses efficiency analysis: Slack Based Model to measure an efficiency score and dynamic panel regression: Generalized Method of Moments to maintain a correlation between fiscal decentralization and efficiency score. This study uses the environmental quality index and regional budget expenditure as analytical fiscal variables. The results show that the original regional income positively affects the efficiency of green development. Meanwhile, provincial spending and population have negatively affected green development efficiency. The influence is due to behavior where in the short term, the region that has just been built will have an impact on reducing the efficiency level, then gradually increasing efficiency driven by the presence of local indigenous income. The uncited form of spending from local governments sometimes only focuses on the orientation of economic growth and physical achievement to slightly ignore the environmental aspect.